A case study on copper-oxide nanofluid in a back pipe vacuum tube solar collector accompanied by data mining techniques. (April 2022) - Sadeghi, Gholamabbas; Najafzadeh, Mohammad; Ameri, Mehran; Jowzi, Mohammad
Abstract: Vacuum tube solar collectors have demonstrated reassuring performance for heat production through a thermosyphon principle with the cold fluid sinking down; however, the fluid remains stagnant at the bottom parts of the tubes where the direction of fluid velocity changes. Researchers have recently declared that removing this region can involve more volume of the fluid in the convective heat transfer process and tangibly contribute to the thermal performance of such collectors. In this study, a back pipe has been adopted to remove this stagnant region by linking the tank to the end of the tube as well as the impacts of multiple back pipe diameters, tank volumes, and copper-oxide/water nanofluid were investigated using outdoor experiments. The results revealed this modification led to decreasing heat losses and improving heat transfer rate by 42% and 10%; respectively, and the optimum aspect ratio of the collector was obtained. Thereafter, two regression techniques including Multi-variate Adaptive Regression Spline and M5 Model Tree were employed to formulate the daily performance of the system for facilitating future investigations on this solar thermal technology. Lastly, the accuracy of understudy techniques was assessed and the presented correlations had a reasonable agreement with the experimental data indicating marginal over/underprediction.